2021
DOI: 10.3390/nu13103353
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Picolinate Improves Bone Formation by Regulation of RANK/RANKL/OPG and BMP-2/Runx2 Signaling Pathways in High-Fat Fed Rats

Abstract: Magnesium (Mg) deficiency may affect bone metabolism by increasing osteoclasts, decreasing osteoblasts, promoting inflammation/oxidative stress, and result in subsequent bone loss. The objective of the present study was to identify the molecular mechanism underlying the bone protective effect of different forms of Mg (inorganic magnesium oxide (MgO) versus organic magnesium picolinate (MgPic) compound) in rats fed with a high-fat diet (HFD). Forty-two Wistar albino male rats were divided into six group (n = 7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…In addition, IL-6 acts as a BMP-2 or OPG/RANKL inhibitor, interfering with the activity of osteoblasts. In the present study, after a bone fracture, the level of proinflammatory cytokines increased, but BP was shown to regulate them due to its polyphenolic compounds, thereby strengthening the process of osteogenesis (Arafa et al, 2023; Sahin et al, 2021). Based on the results obtained, it appears that BP may be useful for treating bone fractures and even for preventing fractures in individuals who are prone to them, particularly those who are elderly, have low serum calcium levels, postmenopausal women, or have absorption disorders.…”
Section: Discussionmentioning
confidence: 49%
“…In addition, IL-6 acts as a BMP-2 or OPG/RANKL inhibitor, interfering with the activity of osteoblasts. In the present study, after a bone fracture, the level of proinflammatory cytokines increased, but BP was shown to regulate them due to its polyphenolic compounds, thereby strengthening the process of osteogenesis (Arafa et al, 2023; Sahin et al, 2021). Based on the results obtained, it appears that BP may be useful for treating bone fractures and even for preventing fractures in individuals who are prone to them, particularly those who are elderly, have low serum calcium levels, postmenopausal women, or have absorption disorders.…”
Section: Discussionmentioning
confidence: 49%
“…Research has shown that high concentrations of Mg 2+ (>6 mM) or an alkaline environment (pH > 8) can reversibly decrease pro‐osteoclast activity 65 . Mg supplementation suppresses osteoclast formation by increasing serum osteoprotegerin (OPG) concentration and reducing the expression of RANKL (receptor activator of nuclear factor‐κB ligand), RNAK (receptor activator of nuclear factor‐κB, NF‐κB), increasing the OPG/RANKL ratio 66 and ultimately inhibiting RANKL/RANK pathway 67,68 . Zhai et al 69 found that pure Mg leach liquor could inhibit the activation of NF‐κB and decrease the expression of NFATc1, effectively suppressing the activity of osteoclasts in vitro.…”
Section: Mechanism Of Single Alkaline Earth Metal In Osteogenesis And...mentioning
confidence: 99%
“…No presente estudo não avaliamos marcadores séricos ósseos, mas realizamos a análise imunoistoquimica das proteínas RANK, RANKL e OPG, que são frequentemente usadas na avaliação de doenças ósseas e podem fornecer informações valiosas sobre a dinâmica da formação e reabsorção óssea. O sistema RANK/RANKL/OPG, um importante regulador da remodelação óssea parece ser profundamente afetado pela nutrição (45). O RANKL é liberado pelas células da linhagem osteoblástica e liga-se ao seu receptor RANK na superfície das células mieloides, estimulando sua diferenciação em osteoclastos (42).…”
Section: Cálculo Da áRea Total áRea Da Zona Hipertrófica E Espessura ...unclassified